Role of wireless capsule endoscopy in reclassifying inflammatory bowel disease in children - Jodie Ouahed; Mohammad Shagrani; Ana Sant'Anna (Brazilian Society of Pediatrics, 2013)
Objective: To evaluate the role of wireless capsule endoscopy in identifying small bowel lesions in pediatric patients with newly diagnosed colonic inflammatory bowel disease (IBD) type unclassified (IBDU), and to assess whether capsule endoscopy findings result in altered patient management. Methods: Ten pediatric patients recently diagnosed with IBDU through standard investigations were recruited from the pediatric gastroenterology clinic at McMaster Children's Hospital to undergo capsule endoscopy using the Pillcam SBTM (Given Imaging) capsule. Findings consistent with a diagnosis of Crohn's disease required the identification of at least three ulcerations. Results: Three out of ten patients had newly identified findings on capsule endoscopy that met criteria for Crohn's disease. Three more patients had findings suspicious for Crohn's disease, but failed to meet the diagnostic criteria. Three additional patients had findings most consistent with ulcerative colitis, and one had possible gastritis with a normal intestine. Findings from capsule endoscopy allowed for changes in the medical management of three patients. In all ten cases, capsule endoscopy allowed for a better characterization of the type and extent of disease. No adverse outcomes occurred in the present cohort. Conclusion: This prospective study reveals that wireless capsule endoscopy is feasible, valuable, and non-invasive, offering the ability to potentially better characterize newly